Functional Disorganization of Small-World Brain Networks in Patients With Ischemic Leukoaraiosis - Zhu, Yixin; Lu, Tong; Xie, Chunming; Wang, Qing; Wang, Yanjuan; Cao, Xuejin; Su, Yuting; Wang, Zan; Zhang, Zhijun (Frontiers in Aging Neuroscience, 2020)
Cognitive impairment is a key clinical feature of ischemic leukoaraiosis (ILA); however the underlying neurobiological mechanism is still unclear. ILA has been associated with widespread gray and white matter damage mainly located in cortical-cortical and cortico-subcortical pathways. A total of 36 patients with ILA (Fazekas rating score ≥ 2) and 31 healthy controls underwent comprehensive neuropsychological assessments (covering 4 cognitive domains, i.e., information processing speed, episodic memory, executive and visuospatial function) and resting-state functional MRI scans. Graph theory-based analyses were employed to explore the topological organization of the brain connectome in ILA patients, and we further sought to explore the associations of connectome-based metrics and neuropsychological performances. An efficient small-world architecture in the functional brain connectome was observed in the ILA and control groups. Moreover, compared with the healthy controls, the ILA patients showed increased path length and decreased network efficiency (i.e., global and local efficiency) in their functional brain networks. Further network-based statistic analysis revealed a functional-disconnected network in ILA, which is comprised of functional connections linking different brain modules (i.e., default mode, frontoparietal, ventral attention and limbic systems) and connections within single modules (i.e., ventral attention and limbic systems). Intriguingly, the abnormal network metrics correlated with cognitive deficits in the ILA patients. Therefore, our findings provide further evidence to support the concept that ILA pathologies could disrupt brain connections, impairing network functioning and cognition via a “disconnection syndrome”.